Characterisation of woven flax fibres reinforcements: Effect of the shear on the in-plane permeability. (November 2015) - Liotier, Pierre-Jacques; Govignon, Quentin; Swery, Elinor; Drapier, Sylvain; Bickerton, Simon
This paper describes a method to characterise the influence of in-plane shear on the permeability of fibrous preforms used in liquid composite moulding processes. An optical method for measuring the local shear variation of the woven textile is presented and used in conjunction with an in-plane permeability measurement system. Two flax fibre fabrics were tested and compared with a woven glass fibre fabric of similar architecture. The system presented here can be used either as a validation tool for permeability prediction models or to compile semi-empirical permeability models for the use in liquid composite moulding process simulation tools.